Consensus Recommendations for the Reconstitution and Aesthetic Use of Poly-D,L-Lactic Acid Microspheres – Comment on the Reason of “Fast Reconstitution” [Letter] - Lin JY; Lin CY (Clinical, Cosmetic and Investigational Dermatology)
Jui-Yu Lin, Chuan-Yuan Lin Li-An Medical Clinic, Taipei City, 104452, TaiwanCorrespondence: Chuan-Yuan Lin, Li-An Medical Clinic, 4F., No. 267, Lequn 2 nd Road, Zhongshan Dist, Taipei City, 104452, Taiwan, Tel +886-939642621, Email linchuanyuan@doctortou.com